Keberterimaan Mahasiswa Jurusan Akuntansi terhadap Pembelajaran Online pada Masa Pandemic Covid-19 - Andi Nurul Istiyana; Fatmawati Fatmawati (AKUNSIKA: Jurnal Akuntansi dan Keuangan, 2020)
Nowdays, world was shocked by a corona virus, then WHO established this condition as a pandemic. This condition has a major impact on various sectors, as well as education. Therefore Minister of Education and Culture of the Republic of Indonesia released decreet about The learning system through online learning is a personal computer (PC) device connected to an internet. The change of learning process, has an impact to student accepetence.This research is explanatory research, to explain the causal relationship between the research variables and test the hypotheses that were formulated. Based on the TAM Model developed by Davis in 1989, testing the user's acceptance of an information system technology. The population used is Accounting Department student’s class of 2019-2020 Politeknik Negeri Ujung Pandang. Purposive sampling is used for sampling. The data collection technique used the distribution of questionnaires with 150 samples. The result was tested by SEM PLS.The results of this study indicate that Accounting Department students accept online learning well. This indicated by all the hypotheses in this study which are accepted. Accounting Department students who were sampled in this study were generation Z who were sensitive to technology.